Pengaruh Opini Audit Terhadap Earnings Response Coefficient: Studi Empiris Pada Perusahaan Yang Termasuk Dalam Indeks Kompas 100 Tahun 2009 - Osesoga, Maria Stefani; Ardianto, Jimmy (Universitas Multimedia Nusantara, 2011)
The users of financial statements require quality and relevant earnings information to be used in decision-making process. The purpose of this study is to determine the significant effect of audit opinion information that contained in the companies' annual report against the quality and relevance earnings information, which measured by Earning Response Coefficient or ERC. This research used control variables, which are beta, leverage, and PBV. The tests conducted in this study were normality test using normal probability plot, the autocorrelation test using Durbin-Watson, multicollinearity test using the value of tolerance and VIF, and heteroscedasticity test using the scatter plot graphic. The hypotheses were tested by using multiple regressions. The results of the study showed that PBV had significant impact on ERC, and indicated that investors had not appreciated the audit opinion information disclosed by the companies in their annual reports for their investment decision. Keywords: Audit Opinion, Beta, Earnings Response Coefficient, Leverage, Price to Book Value.